Kualitas Produk dan Harga Dalam Meningkatkan Minat Pembelian Konsumen Pada Rebana NS Di Kabupaten Gresik - Muchsin Zuhad Al'asqolaini; Ahmad Junaidi Musthofa (Universitas Pendidikan Nasional, 2020)
The purpose of this study is to determine the effect of Product Quality and Price on Consumer Purchase Interests in Tambourine NS, and to analyze the effect partially and simultaneously of each variable, so that the data analysis method used is to use multiple linear regression analysis and hypothesis testing with test t and F test. In this study, the population was 35 regular customers of tambourine NS products using saturated samples. Data collection was carried out by giving a list of questions to respondents, namely regular customers tambourine NS. Based on the results of the analysis of multiple linear regression tests produce that Product Quality and Price Simultaneously influence 7.625 with a significance of 0.000. While the partial test results of Product Quality partially influence 4,322 with a significance of 0,000 results. another case with Prices which partially does not affect the Consumer Purchase Interest. The most dominant variable in influencing consumer purchase interest is product quality.